A kinematic analysis of mandibular border movements in patients with craniomandibular disorderds - Dodić Slobodan; Sinobad Vladimir (Serbian Medical Society - Dental Section, Belgrade, 2003)
Disturbances in mandibular kinematics are supposed to be one of the main signs of craniomandibular disorders (CMD). In that regard, recordings of mandibular border movements may offer valuable data in assessing functional efficiency of the OF complex, as well as in diagnosing CM disorders. The electronic pantograph Arcus Digma (Kavo EWL GmBH, Leutkirch, Germany) was used in this study to record and evaluate the trajectories of the interincisal point in three planes during mandibular protrusion laterotrusion and mouth opening. Two groups of volunteers between 18 and 26 years of age were established for this investigation: one consisting of persons with signs (symptoms) of CMD and the other of persons without such signs and symptoms. The results of this study point out the significant differences in the length and shape of interincisal point tracings in the horisontal plane, as well as in angulation of laterotrusive tracings between the examined groups. The reduced mandibular opening was established in 17% of females and 13% of males in the group presenting the signs (symptoms) of CMD.